Persuasion with communication costs - Hedlund, Jonas (Games and economic behavior, 2015)
This paper studies strategic transmission of verifiable information with reporting costs that continuously increase in the precision of the report. Contrary to previous literature, it is shown that the unraveling result first derived by Milgrom (1981) is relatively robust to costly reporting. A separating equilibrium exists even with arbitrarily high reporting costs. Intuitively, the costs work as a signaling device and a combination of disclosure of information and costly signaling accomplishes full separation. With reporting costs there are typically multiple equilibria. For example, a pooling equilibrium exists if and only if the reporting costs are high. Finally, a separating equilibrium exists when the receiver has to make a costly effort in order to access the information in a report, as long as this cost is not too high.